2022
DOI: 10.1161/circep.121.010663
|View full text |Cite
|
Sign up to set email alerts
|

90 vs 50-Watt Radiofrequency Applications for Pulmonary Vein Isolation: Experimental and Clinical Findings

Abstract: BACKGROUND: Fifty-watt radiofrequency applications have proven to be safe and efficient for pulmonary vein isolation (PVI). However, as PV reconnection still occurs and ablation catheter instability significantly contributes to suboptimal lesion formation, a new ablation catheter capable of delivering 90 W for 4 seconds only has been developed with the aim of improving PVI outcomes. In this setting, we sought to determine whether 90 W applications create transmural lesions without collateral damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 10 publications
5
74
2
Order By: Relevance
“…Within our relatively small sample population, we also realized a statistically non-significant tendency towards time-saving within the other measured procedural times (left atrial dwell time, total procedure time and fluoroscopy time). These later findings are similar but not totally in line with the results of Bortone et al, showing that within their cohort, 90 W 4 s PVI ablation led to similar procedural times due to a lower first pass PVI-rate and higher acute PV reconnection rate [ 10 ]. The minor differences between the results of those two studies might be caused by the relatively small study population size but might partly be explained by the fact that the 90 W 4 s protocol is much more prone to suboptimal lesion formation in cases of an unstable ablation catheter position during RF-energy application.…”
Section: Discussionsupporting
confidence: 83%
“…Within our relatively small sample population, we also realized a statistically non-significant tendency towards time-saving within the other measured procedural times (left atrial dwell time, total procedure time and fluoroscopy time). These later findings are similar but not totally in line with the results of Bortone et al, showing that within their cohort, 90 W 4 s PVI ablation led to similar procedural times due to a lower first pass PVI-rate and higher acute PV reconnection rate [ 10 ]. The minor differences between the results of those two studies might be caused by the relatively small study population size but might partly be explained by the fact that the 90 W 4 s protocol is much more prone to suboptimal lesion formation in cases of an unstable ablation catheter position during RF-energy application.…”
Section: Discussionsupporting
confidence: 83%
“…For HPSD lesions, the temperature‐controlled QMODE algorithm is used, which modulates irrigation rate (first) and power (afterward, if irrigation rate increase is not enough) based on temperature, allowing for the creation of lesions of up to 50 W. The information is also integrated into the electromagnetic location technology of CARTO3® mapping system (Biosense Webster Inc). Although not developed or validated for QDot‐Micro catheter, AI can be calculated for applications performed with the QMODE algorithm (but not whit QMODE+), and some groups have tested its clinical performance, with good results 11–13 . We employed the same AI objectives that have been proposed for left atrial posterior (400) or anterior (550) wall ablation when using QDot‐Micro for conventional to high‐power lesions (up to 50 W).…”
Section: Methodsmentioning
confidence: 99%
“…Although not developed or validated for QDot-Micro catheter, AI can be calculated for applications performed with the QMODE algorithm (but not whit QMODE+), and some groups have tested its clinical performance, with good results. [11][12][13] We employed the same AI objectives that have been proposed for left atrial posterior (400) or anterior (550) wall ablation when using QDot-Micro for conventional to high-power lesions (up to 50 W).…”
Section: Catheter Descriptionmentioning
confidence: 99%
“…Therefore, 90 W/4 s‐vHPSD ablation has been reported to be suitable for thin‐walled structures such as the human atrium, with the walls of the PV in humans being very thin, measuring 0.82–1.24 mm on computed tomography 18–20 and 1.7–2.8 mm on autopsy 21 . Nonetheless, a recent study of Bortone et al showed a significantly lower rate of a first‐pass PVI with 90 W/4 s‐vHPSD ablation than 50 W HSPD ablation (37/75 [49.3%] vs. 61/75 [81.3%], p < .001) 22 . The failure sites of the first‐pass PVI were mostly the PV carina regions, which are known as thickened veno‐atrial junction sites 18–20 .…”
Section: Discussionmentioning
confidence: 99%
“…16,17 We did not incorporate catheter orientation into our in vivo assessment, but most target sites were not perpendicular to the catheter tip, explaining, at least in part, why shallow and relatively wide lesions p < .001). 22 The failure sites of the first-pass PVI were mostly the PV carina regions, which are known as thickened veno-atrial junction sites. [18][19][20] Therefore, shallower lesions with the 90 W/4 s-vHPSD ablation implicated that this ablation setting might not be sufficient for thick atrial walls.…”
Section: Relation Between Tissue Temperatures and Pathological Findingsmentioning
confidence: 99%